RETRACTED ARTICLE: Burnout components, perceived stress and hair cortisol in healthcare professionals during the second wave of COVID 19 pandemic - F. Fortuna; D. Gonzalez; A. Fritzler; C. Ibar; G. Nenda; E. D’Isa; P. Otero; J. Jamardo; M. Calvo; F. Funez; F. Minotti; L. Filipuzzi; et al. (Scientific Reports)
Abstract This study evaluates the impact of the COVID-19 pandemic on healthcare workers in Argentina, during the second wave in 2021. The aim is to assess stress and burnout, incorporating the assessment of hair cortisol levels as a biomarker of chronic stress. A total of 496 healthcare workers from three different hospitals were included in this study. Two of these hospitals depend on the Buenos Aires City Ministry of Health and the third hospital belongs to Buenos Aires University. Hair samples were obtained using scissors from the posterior vertex, as close to the scalp as possible. Each sample was weighed, and cortisol was extracted and then measured using an automated chemiluminescent method. Notably, 10% of the population exhibited hair cortisol levels above 128 pg/mg. Associations were found between high hair cortisol levels and age, workload, emotional exhaustion, and depersonalization. In addition, burnout, identified in 11% of participants, correlated with higher perceived stress and lower social support. Binary logistic regression revealed associations between burnout and perceived stress, and age. Finally, mediation analysis showed depersonalization as a mediating variable in the relationship between hair cortisol concentration and emotional exhaustion. In conclusion, this study highlights the complex relationships between stress, cortisol levels, and burnout. Prioritizing interventions and research is essential to support the well-being of frontline healthcare professionals, ensuring their resilience during challenging times.